Microalloying by aluminum of the construction low-alloy steel with the purpose of increase of cold-resistance of casts - V. G. Babkin; A. V. Dobrynina (Литьë и металлургия, 2002)
In the article there are given the results of investigation on important matter — cold-resistance of building steel 20 GL. There are given the explanations of effects occurring in steel during the process of thermal treatment at changing of its chemical composition.